Enhancing Critical Media Ethics in EFL Classrooms through Fake News Deconstruction, Narrative Reframing, and Editorial Simulation - Margaret Stevani; Alexander Adrian Saragi; Oktaviana Maria Fatima Queiros Bobe; Happy Kusuma Wardani (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study explored how integrating fake news deconstruction, narrative reframing, and editorial simulation enhanced critical media ethics in EFL classrooms. Moving beyond conventional language instruction, it positioned English learning as a site of ideological negotiation and epistemic responsibility. Thirty education students as teacher candidates in North Sumatra engaged in an eight-week task-based curriculum analyzing ethically problematic texts drawn from real-world media. Guided by systemic functional linguistics, critical discourse analysis, and appraisal theory, students rewrote distorted headlines, clarified vague attributions, and reconstructed visual-caption misalignments. Findings revealed that students developed rhetorical precision, ethical awareness, and stylistic maturity, transforming from passive consumers into critical and active media agents. By combining language learning with civic literacy, this study proposed a replicable model for ethical pedagogy in digital times, foregrounding truth-validation, genre critique, and linguistic agency as core components of 21st-century EFL education.